PENGEMBANGAN STRATEGI PARIWISATA BERKELANJUTAN DESA WISATA DI YOGYAKARTA MELALUI ANALISIS SWOT (MATRIKS KUADRAN SWOT DAN EFAS &IFAS) - Rubiyatno, Rubiyatno; Kurniawati, Lucia; Pranatasari, Fransisca Desiana (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
Indonesia and tourism are an inseparable and mutually synergistic unit that has the potential to become a competitive advantage for Indonesia. Tourism Villages present an overall atmosphere that reflects rural authenticity in terms of social, economic, cultural, daily life, customs, has unique architecture and spatial planning. distinctive and unique, or economic activities that are unique and interesting and have the potential to develop tourism components. This research aims to provide recommendations for developing strategies for the potential of tourist villages through SWOT analysis with matrices, quadrants and EFAS&IFAS. The goal is to achieve sustainable tourism in the Special Region of Yogyakarta. This research is a qualitative descriptive research. Observation, interview and literature study methods were used to obtain information about tourism potential. Qualitative descriptive analysis was used to formulate a Tourism Development Strategy in the Special Region of Yogyakarta based on SWOT Analysis. As a result, tourist villages can utilize recommended tourism village development strategies to achieve sustainability Keywords: Strategy, tourist villages, tourism, sustainable tourism, SWOT analysis